Pengaruh IQ (Intelligence Quotient) Dan EQ (Emotional Quotient) Terhadap Pengambilan Keputusan Pejabat Pengadaan/Pokja Pemilihan Pada Proses Pengadaan Barang/Jasa Pemerintah Di Kabupaten Pangandaran - Dede Heryanto (Politeknik Kampar, 2023)
This article is to determine the effect of IQ (Intelligence Quotient) and EQ (Emotional Quotient) on the decision making of procurement officials/selection working groups in the process of procuring goods/services in Pangandaran district. Procurement of Government Goods/Services is the activity of procuring goods/services by Ministries/Institutions/Regional Apparatuses financed by the APBN/APBD whose process starts from identification of needs to the handover of the work. Human Resources in Government Goods/Services Procurement, namely Procurement Officers/Selection Working Groups who have the skills to determine providers who are able to work on work packages. This can be viewed in terms of IQ (Intelligence Quotient) and EQ (Emotional Quotient). This study aims to determine (1) The effect of IQ (Intelligence Quotient) on the Decision Making of Procurement Officials/Election Working Groups in the Government Procurement of Goods/Services. (2) The Influence of EQ (Emotional Quotient) on the Decision Making of Procurement Officials/Election Working Groups in the Government Procurement of Goods/Services. (3) The simultaneous influence of IQ (Intelligence Quotient) and EQ (Emotional Quotient) on the Decision Making of Procurement Officials/Election Working Groups in the Government Procurement of Goods/Services. The method used in this study is a quantitative method by analyzing the data from the questionnaire. The results of the study show that: (1) There is a positive and significant influence of IQ (Intelligence Quotient) on the Decision Making of Procurement Officials/Election Working Groups in the Government Procurement of Goods/Services. (2) There is a positive and significant influence of EQ (Emotional Quotient) on the Decision Making of Procurement Officials/Selection Working Groups in the Government Procurement of Goods/Services; (3) There is a positive and significant influence of IQ (Intelligence Quotient) and EQ (Emotional Quotient) simultaneously on the Decision Making of Procurement Officers/Election Working Groups in the Government Procurement of Goods/Services.